European Neuroendocrine Tumor Society (ENETS) 2024 guidance paper for the management of well-differentiated small intestine neuroendocrine tumours - Lamarca, Angela; Bartsch, Detlef K.; Caplin, Martyn; Kos-Kudla, Beata; Kjaer, Andreas; Partelli, Stefano; Rinke, Anja; Janson, Eva Tiensuu; Thirlwell, Christina; van Velthuysen, Marie Louise F.; Vullierme, Marie Pierre; Pavel, Marianne Ellen (Journal of Neuroendocrinology, 2024)
Both the incidence and prevalence of well-differentiated neuroendocrine tumours from the small intestine (Si-NET) are gradually increasing. Most patients have non-functioning tumours with subtle GI symptoms and tumours are often discovered incidentally by endoscopy or at advanced disease stages by imaging depicting mesenteric lymph node and /or liver metastases while around 30% of the patients present with symptoms of the carcinoid syndrome. Adequate biochemical assessment and staging including functional imaging is crucial for treatment-related decision-making that should take place in an expert multidisciplinary team setting. Preferably, patients should be referred to specialised ENETS Centres of Excellence or centres of high expertise in the field. This guidance paper provides the current evidence and best knowledge for the management of Si-NET grade (G) 1–3 following 10 key questions of practical relevance for the diagnostic and therapeutic decision making.
CRIS-Team Scopus Importer:2024-07-19
Keywords: guidance; neuroendocrine; small intestine; treatment